Successful treatment of metastatic bladder cancer by gemcitabine‐cisplatin re‐challenge after pembrolizumab. Issue 6 (20th July 2021) - Arai, Takayuki; Takeuchi, Nobuyoshi; Sazuka, Tomokazu; Sato, Hiroaki; Imamura, Yusuke; Sakamoto, Shinichi; Komiya, Akira; Ichikawa, Tomohiko
Abstract : Introduction: The advent of pembrolizumab has contributed to improved treatment outcomes for metastatic urothelial carcinoma, but the outcomes of treatments after second‐line treatment have not been established. Case presentation: A 72‐year‐old man was referred to our hospital with gross hematuria and diagnosed with suspicion of bladder cancer cT1N0M0. Transurethral resection of the bladder tumor was performed, but local recurrence and multiple lung metastases appeared 5 months after surgery. Although gemcitabine‐cisplatin was performed as first‐line chemotherapy, the local lesion increased, and pembrolizumab was used as a second‐line treatment. Pembrolizumab was also ineffective; however, re‐challenge with gemcitabine‐cisplatin as third‐line treatment produced a good therapeutic effect. Conclusion: We report a successful case in which gemcitabine‐cisplatin re‐challenge after pembrolizumab therapy was effective in metastatic bladder cancer. Re‐administration of chemotherapy after immune checkpoint inhibitors may be a broadly effective treatment option.